Short- and long-term risks of photoselective laser vaporization of the prostate: a population-based comparison with transurethral resection of the prostate - Salmivalli Alisa; Ettala Otto; Nurminen Pertti; Kinnala Pekka; Boström Peter; Kytö Ville (TAYLOR & FRANCIS LTD, 2025)
Background Transurethral resection of the prostate (TURP) is the standard surgical treatment for benign prostate enlargement (BPE). Photoselective vaporization of the prostate (PVP) is an alternative, but there is limited real-life evidence of PVP risks. Objective To compare short- and long-term risks of PVP to those of TURP in the treatment of BPE. Materials and methods Consecutive patients who underwent elective PVP or TURP between 2006 and 2018 in 20 hospitals in Finland were retrospectively studied using a combination of national registries (n = 27,408; mean age 71 years). Short-term risks were postoperative mortality, major adverse cardiovascular events (MACE), and reoperations for bleeding. Long-term risks were reoperations for BPE or any urethral operations within 12 years. Differences between treatment groups were balanced by inverse probability of treatment weighting. Risks were analyzed using the Kaplan-Meier method and Cox regression. Results There were no differences in postoperative mortality or MACE between the study groups. Reoperations for bleeding were less frequent after PVP (0.9%, HR: 0.72, p = 0.042). Bleeding was more likely in patients with atrial fibrillation (number needed to treat [NNT] for PVP vs TURP: 61). Cumulative incidence for reoperation was higher after PVP (23.5%) than after TURP in long-term follow-up (17.8%; HR: 1.20, p < 0.0001, NNT: -31.7). Conclusions PVP is associated with lower postoperative bleeding risk but higher long-term reoperation risk than TURP. Patients with high bleeding risk and a low likelihood of needing reoperation appear most suitable for laser vaporization. KEY MESSAGE PVP is associated with lower postoperative bleeding risk but higher long-term reoperation risk than TURP. PVP appears an attractive treatment option, especially for patients with high bleeding risk and a low likelihood of needing a reoperation.